2014
DOI: 10.1016/j.abb.2014.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Targeting melanocyte and melanoma stem cells by 8-hydroxy-2-dipropylaminotetralin

Abstract: Monobenzyl ether of hydroquinone (MBEH) is cytotoxic towards melanocytes. Its treatment efficacy is limited by an inability to eradicate stem cells. By contrast, 8-hydroxy-N,N-dipropyl-2-aminotetralin (8-DPAT) affects melanocyte stem cell survival. MBEH and 8-DPAT were added to melanocytes and melanoma cells to compare cytotoxicity. Stem cell content among viable cells was determined by fluorocytometry using markers CD34, Pax3, and CD271. Immunostaining was used to identify stem cells in skin explants treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Monobenzone or monobenzyl ether hydroquinone (MBEH) is a topical agent approved by the US Food and Drug Administration (FDA), which is used to even the skin tone providing pigment loss by damaging the melanocytes in unaffected areas of vitiligo patients who have widespread (over more than 50% of their skin) depigmentation problem. [18][19][20] Pigment loss due to contact with MBEH is clinically and histologically similar to vitiligo. It has been observed that healthy people who topically apply MBEH to lighten their skin tone develop the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Monobenzone or monobenzyl ether hydroquinone (MBEH) is a topical agent approved by the US Food and Drug Administration (FDA), which is used to even the skin tone providing pigment loss by damaging the melanocytes in unaffected areas of vitiligo patients who have widespread (over more than 50% of their skin) depigmentation problem. [18][19][20] Pigment loss due to contact with MBEH is clinically and histologically similar to vitiligo. It has been observed that healthy people who topically apply MBEH to lighten their skin tone develop the disease.…”
Section: Discussionmentioning
confidence: 99%
“…27,35,37,38 On the other hand, hydroquinone (C 6 H 6 O 2 ) possesses intracellular cytotoxic effect that reduces pigmentation level by nonselectively destroying the epidermal melanocytes and keratinocytes. [39][40][41] Due to aggressive mode of action of hydroquinone in reducing level of pigmentation, it is associated with skin cancer. 40,41 In recent years, cosmetic products containing hydroquinone have been banned in most countries, but its usage for medical purpose can be compromised under strict regulation.…”
Section: F I G U R E 1 Multiple Conversion Of Phenylalanine To Eumelamentioning
confidence: 99%
“…Previously known depigmenting compounds such as azelaic acid (C 9 H 16 O 4 ) selectively reduce hyperpigmentation in abnormal melanocytes, and it has minimum effect to normal melanocytes . On the other hand, hydroquinone (C 6 H 6 O 2 ) possesses intracellular cytotoxic effect that reduces pigmentation level by nonselectively destroying the epidermal melanocytes and keratinocytes . Due to aggressive mode of action of hydroquinone in reducing level of pigmentation, it is associated with skin cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Replacing the mammalian model with the zebrafish embryo model for evaluation of efficacy and safety of depigmenting compounds is an interesting topic of discussion in the skin-care industry [ 73 , 74 , 75 , 92 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ]. However, in the cosmetic or even dermatological industry, these compounds are formulated in combination of a carrier or vehicle to facilitate its effect on human skin [ 73 , 74 , 79 , 86 , 115 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…Regardless of its applications and benefits, skin depigmentation may also give adverse effect especially over long period of time. Melanin is a photoprotective component, and plays a physiological role as a UV absorbent, which is known to protect skin from harmful and excessive UV radiation intensity, DNA damage as well as development of cancer cells [ 1 , 16 , 114 , 116 ]. Melanin during melanogenesis, enzymes such as catalase, glutathione peroxidase and superoxide dismutase are synthesized and dedicated to removing radicals [i.e., reactive oxygen radical (ROS), superoxide anion (O 2 •- ), hydrogen peroxide (H 2 O 2 ), and singlet oxygen ( 1 O 2 )] [ 1 , 16 ].…”
Section: Skin Depigmentation: Pros and Consmentioning
confidence: 99%